Optimizing Ore Recovery in Shallow-Dipping Orebodies (45-60 deg): A Framework for Stope Design, Drill and Blast, and Equipment Selection - Gurupraveen Ramanathan (Canadian Institute of Mining, Metallurgy and Petroleum, 2025)
Shallow-dipping orebodies (45°–60° dip) present significant challenges for underground longhole stoping, particularly due to limited gravity flow, drill misalignment near the footwall, increased potential for dilution from hanging wall overbreak, and deviation from drill string sagging at shallow angles. These geometrical and operational constraints often lead to unblasted ore wedges and excessive overbreak when standard practices are applied. This study develops a structured, data-driven framework to optimize longhole stoping in such conditions by integrating five key focus areas: (1) mining method selection, (2) stope and drift design, (3) drill and blast optimization, (4) equipment selection, and (5) performance evaluation. The suitability of longitudinal longhole stoping was validated for narrow vein geometries using orebody analytics and prior case studies. Geometric modeling was employed to determine optimal stope height (15–20 m) and stope width (1.5–2.5 m), with drift widths adjusted based on orebody dip to maintain drill access and minimize unbroken ore. Drill and blast design emphasized sequential blasting over multi-ring methods to improve void control, reduce wall damage, and enhance fragmentation. Specific burden and spacing guidelines (e.g., 1.8–2.3 m burden; 2.5–3.0 m spacing) were applied based on stope width and dip angle, and patterns were selected based on geometry—dice-5 for narrow stopes, and 3-hole rows for wider stopes. Drill rigs—including top hammer and ITH models from Sandvik, Epiroc, Boart Longyear and CMAC-Thyssen—were evaluated for compatibility with drift dimensions and alignment accuracy. Equipment was matched based on dip, drift width, and the ability to access the footwall at shallow angles. Sensitivity analysis quantified how changes in geometry, drilling accuracy, and blast design affect ore recovery, dilution, and operating cash flow. Results show that tailored drift and stope geometries, combined with proper blasting and rig selection, can boost ore recovery to over 95% and reduce dilution to below 5% in optimal conditions. This methodology offers a practical and economically optimized solution for shallow-dip mining scenarios.